Cartoon Violence, Aggression And Imagination: In-Depth Interview With The Reference Of Two Girls - Pant, Swati; Kumar Pal, Arvind (International Journal of Psychosocial Rehabilitation, 2020)
Children’s life without cartoons are impossible. Big eyes, wired smile, unstoppable action and so on, these are enough to attract any kid. Children need someone they can relate to in today’s world where everyone is busy achieving their ambitions. Cartoon viewing has an impact on a child’s behavior, including their likes and dislikes, walking and talking patterns, and interactions with other children and adults. This research study is explorative. It mainly focuses on two girls who are heavy viewer of cartoon. Both respondents were interviewed and observed by their parents during covid scenario. For study purpose psychologist is also approached. “Behavior assessment scale for children with reference of aggression” (BASC aggression) test was done. The major findings shown both respondents highly impacted with cartoons. They are very reserve and scared of new people or world.